Analytical and Experimental Investigation of the Impact of Land Reclamation on Steady‐State Seawater Extent in Coastal Aquifers. Issue 6 (10th June 2021) - Zhang, Jia; Lu, Chunhui; Werner, Adrian D.
Abstract: Previous studies of the effects of land reclamation on the extent of seawater in coastal aquifers have assumed that the reclaimed area penetrates to the impermeable base of aquifer, and that the seawater in the aquifer is entirely contained within reclaimed sediments. The current study extends previous research into the effects of reclamation on groundwater levels and seawater extent by developing new analytical expressions for the steady‐state heads and non‐dispersive freshwater‐seawater interface for situations where reclaimed soils overly permeable aquifer material. Situations involving reclaimed soils that are more permeable or less permeable than the original aquifer are explored. Sand‐tank experiments and associated numerical simulations (in 2D cross section) were undertaken to evaluate assumptions adopted in developing the solutions, which include an empirical correction to account for dispersion effects. Sand tank solute distributions are well matched to numerical modeling results, and provide validation of analytical solutions and the associated simplifications. Application of the new solution demonstrates that both the water level rise and the seaward shift of seawater extent caused by reclamation are modified with the inclusion of the underlying permeable layer, depending on permeability contrasts and the reclaimed area size. For example, if the reclaimed soil is less permeable than the original aquifer, water level rise and the seawater extent shift are reduced with the inclusion of an underlying permeable layer. The analytical solution developed in this study can provide rapid guidance on the changes to seawater extent and groundwater levels caused by land reclamation in otherwise permeable substrate. Key Points: Analytical solution developed to estimate seawater extent changes from land reclamation in otherwise permeable sediment The seaward shift in seawater extent and the head rise caused by reclamation are modified by the new coastal boundary A correction factor for sharp‐interface analytical solutions applies to the new land reclamation analytical solutions